Jacques Lacan and feminist epistemology - Campbell, Kirsten, 1969- (Transformations., 2004)
Using Lacanian psychoanalysis as a starting point, Campbell examines contemporary feminism's turn to accounts of feminist 'knowing' to create new conceptions of the political.